WOMEN LEADERSHIP AND WOMEN’S LEGISLATIVE REPRESENTATION: THEIR INFLUENCE ON THE PROPORTION OF GENDER RESPONSIVE BUDGETING - Suci Nurul Khotimah; R. Muh. Syah Arief Atmaja Wijaya (JAT : Journal Of Accounting and Tax, 2026)
This study looks at how women's leadership and legislative participation affect the percentage of gender-responsive budgeting in East Java Province's regencies and municipalities between 2023 and 2025. Using secondary data from the Regional Revenue and Expenditure Budget (APBD), Regional Government Work Plans (RKPD), and official records of female regional leaders and legislators, this study uses a quantitative explanatory approach. There are 39 local governments in the sample. EViews 12 was used to do panel data regression analysis. The results show that the percentage of gender-responsive budgeting is not considerably impacted by women's leadership, suggesting that institutional and political barriers prevent women in executive roles from automatically increasing the allocation of gender-oriented budgets. On the other hand, gender-responsive budgeting is positively and significantly impacted by women's legislative representation, highlighting the significance of increasing women's involvement in regional government to promote more inclusive and equitable development results. These results imply that obtaining more equitable public policy outcomes at the local government level and promoting gender-responsive budgeting depend on increasing women's political representation in legislative institutions.